The alteration on the spatial elements of Traditional Malay House at heritage village of Malacca / Yasmin Nur Amirah Yaman, Rohaslinda Ramele and Nor Rima MuhamadAriff - Yaman, Yasmin Nur Amirah; Ramele, Rohaslinda; MuhamadAriff, Nor Rima (2019)
Traditional Malay house (TMH) known as a vernacular architecture, which is designed harmoniously based on the socioeconomic, cultural and environmental needs. However, rapid development has influenced and modernized the original architecture of TMH and affected the styles, characters and functions of the TMH. The change of spatial element has caused the changes in living conditions that requires the alteration of original construction of the house. This paper aims to clarify the internal spatial elements of spaces and functions of TMH at heritage village in Malaysia and to explore the factors of alteration done. The significance of this research is to highlight the problems that occurred in TMH and to preserve the architectural of TMH from disappear in the future. Field investigations and observations were conducted at selected eight traditional Malay houses in Kampung Sidang Seman. Findings showed the existing spatial elements of rumah ibu or rumah dapur still can be seen at the most of the houses either the structures on stilts or on ground level. Furthermore, most of these spaces have altered their functions into private area and extend their house based on their basic need.